Factors that influence access to mental health services in South-Eastern Europe - Andreea Raluca Tirintica (International Journal of Mental Health Systems, 2018)
Abstract Introduction Access to mental health (MH) services is unequal worldwide and changes are required in this respect. Objectives Our aim was to identify the delay to the first psychiatry consult and to understand patients’ characteristics and perspectives on the factors that may influence the delay, among a sample of participants from three Southeastern European Countries. Materials and methods The WHO Pathway Encounter Form questionnaire was applied in 400 patients “new cases” and a questionnaire on the factors influencing the access was administered to the same patients, as well as to their caretakers and MH providers. Result and discussions The average profile of the patient “new case” was: married female older than 40 years, with an average economic status and no MH history. The mean delay was up to 3 months and the most important factors that were influencing the delay were stigma and lack of knowledge regarding MH problems and available current treatments. Conclusions Future policies trying to improve the access to psychiatric care should focus on increasing awareness about MH problems in the general population.